2014
DOI: 10.1111/tmi.12360
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a school‐based latrine cleaning and handwashing program on pupil absence in Nyanza Province, Kenya: a cluster‐randomized trial

Abstract: Improving school water, sanitation and hygiene (WASH) conditions has been shown to be effective in reducing pupil absence and illness. However, the benefit of sanitation and hygiene promotion improvements at school may depend on the conditions of the latrines and availability of consumables. We employed a three-arm, cluster-randomized trial to determine if a low-cost, policy-relevant, environmental-level latrine cleaning intervention could a) improve latrine cleanliness, b) increase latrine use, and c) reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 29 publications
3
66
1
6
Order By: Relevance
“…Our impact evaluation, like other studies before it, [9][10][11][14][15][16] showed mixed results. We found lower rates of self-reported diarrhea and respiratory infection symptoms among beneficiary schools compared with the comparison schools.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our impact evaluation, like other studies before it, [9][10][11][14][15][16] showed mixed results. We found lower rates of self-reported diarrhea and respiratory infection symptoms among beneficiary schools compared with the comparison schools.…”
Section: Discussionmentioning
confidence: 80%
“…15 Similarly, null findings were found when schools were provided latrine cleaning and handwashing supplies. 16 Poor WASH conditions may be only one barrier to school attendance, and in many contexts, improvements to school facilities, or school WASH in particular, may not be sufficient to overcome other barriers like income generation or domestic tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Recent school WASH trials in Kenya investigated intervention fidelity and adherence and found improvements to WASH infrastructure, but usually not to optimal levels. 4,[13][14][15] The lack of consistent evidence of impact may also be that pupils' health and education are influenced by many other factors that are not related to the WASH conditions in schools, such as socioeconomic factors. Further, without proper pupil behaviors and operation and maintenance of facilities, WASH programs may be insufficient in breaking the transmission cycle and may even increase exposure to fecal pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Improvements to WASH at schools have sometimes been shown to reduce diarrheal disease, 6,9 acute respiratory infections, 10 soil-transmitted helminth reinfections, 11 and absence among pupils. 3,12 However, these effects are often not consistent between studies and within studies they are dependent on study context and/or the subgroup of pupils under study.…”
Section: Introductionmentioning
confidence: 99%
“…Among the articles included after the final screen (n=48), only 12 made some reference to WASH in schools. Of these articles, one focused on hygiene education and latrine cleaning [20], one lists support tools that could be used for WASH in school programs [16], one discussed the benefits of funding school WASH [21], and nine discussed comprehensive WASH (including water supply, sanitation, and hygiene) in schools through a number of case studies in Kenya [22][23][24], the Asian-Pacific region [25], Ethiopia [26], India [27], Uganda [28], Bangladesh [29], and Latin American Countries [30]. These results show a lack of published information around WASH in schools as compared to community WASH.…”
Section: Resultsmentioning
confidence: 99%